"I Was Praying for My Very Salvation from My Sexual Abuse": Experiences of Sexual Abuse Survivors in the Church of Jesus Christ of Latter-Day Saints. Issue 3 (2nd October 2021) - Choruby-Whiteley, Amber; Morrow, Susan L.
Abstract: Researchers have thoroughly documented the experiences of sexual abuse survivors; however, many complications may arise for adult survivors who are religious. To our knowledge, there have been no previous studies regarding childhood sexual abuse survivors who are members of the Church of Jesus Christ of Latter-day Saints. This qualitative research project sought to explore the questions, "What are the gendered messages of femininity that Latter-day Saint childhood sexual abuse survivors have received, and how have these messages impacted their healing from sexual abuse?" Fourteen participants were interviewed as part of a qualitative investigation in a semi-structured format with open-ended questions from an emergent grounded theory design. The researchers analyzed the interviews to reveal results that are grounded in participants' reported experiences. Six themes arose under the category of Harmful Cultural Lesson and Social Norms. An additional theme, Healing through Advocating for Change, presented alongside a theoretical framework of healing, explores the relationship between the harmful cultural messages that Latter-day Saint sexual abuse survivors internalize, the subsequent impact on a survivor's sense of self, and alternative trauma-informed lessons that lead to healing. The author(s) present these results along with the implications for therapists working with Latter-day Saint sexual abuse survivors, recommendations for church policy changes, and future research directions.